The Role of PT Indofood as a Non-State Actor in Supporting Indonesia-Saudi Arabia Gastrodiplomacy through Indomie Products - Irmayanti, Mirza Ayu; Priadarsini, Ni Wayan Rainy; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
This research aims to describe the role of PT Indofood as a non-state actor in supporting gastrodiplomacy in Indonesia and Saudi Arabia through Indomie instant noodle products. Gastrodiplomacy as a culinary diplomacy tool has become an interesting subject in international diplomacy. In this context, PT. Indofood CBP Sukses Makmur Tbk, through its Noodle Division which produces instant noodle products, especially the Indomie brand, has played an important role in promoting Indonesian culinary culture at the international level. In an effort to exploit the potential of gastrodiplomacy, Indonesia has used Indomie as a tool to attract the attention and sympathy of the international community, especially in Saudi Arabia. Through Indomie exports, Indonesia has created an opportunity to communicate its culture and promote its image on the global stage. The strategy involving Indomie exports has been combined with efforts by the Ministry of Trade (Kemendag) to minimize trade barriers, which includes support for national exporters such as PT. Indofood Sukses Makmur Tbk. With the various strategies that have been implemented, Indonesian gastrodiplomacy, especially through superior products such as Indomie, has succeeded in attracting public interest in Saudi Arabia and promoting a better understanding of Indonesia. This success has proven that the role of PT. Indofood Sukses Makmur Tbk as a non-state player has become an integral part of Indonesia's culinary diplomacy and in helping to advance Indonesia's image at the international level. Researchers use the concepts of Gatrodiplomacy and Non-State Actor to explain the role and efforts of PT Indofood in introducing food products from Indonesia. Keywords :   Gastrodiplomacy, Non-State Actor, Indomie, Saudi Arabia